2021
DOI: 10.3389/fimmu.2021.787307
|View full text |Cite
|
Sign up to set email alerts
|

The Colony Stimulating Factor-1 Receptor (CSF-1R)-Mediated Regulation of Microglia/Macrophages as a Target for Neurological Disorders (Glioma, Stroke)

Abstract: Immunomodulatory therapies have fueled interest in targeting microglial cells as part of the innate immune response after infection or injury. In this context, the colony-stimulating factor 1 (CSF-1) and its receptor (CSF-1R) have gained attention in various neurological conditions to deplete and reprogram the microglia/macrophages compartment. Published data in physiological conditions support the use of small-molecule inhibitors to study microglia/macrophages dynamics under inflammatory conditions and as a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 104 publications
0
25
0
Order By: Relevance
“…1 ). The CSF1, under physiological conditions, plays a role in cell survival, proliferation, differentiation, and functions of the mononuclear cells, and therefore its higher expression in patients without cancer is not surprising [ 32 34 ]. Additionally, peripheral blood mononuclear cells (PBMCs) isolated from the blood of healthy individuals and patients with primary (Gleason 6), mid (Gleeson 7), or distant metastasis (Gleason 9) PCa ( n = 2 per condition) showed that both CSF1 and NOS3 were significantly increased ( p < 0.05) in high-grade PCa patients (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). The CSF1, under physiological conditions, plays a role in cell survival, proliferation, differentiation, and functions of the mononuclear cells, and therefore its higher expression in patients without cancer is not surprising [ 32 34 ]. Additionally, peripheral blood mononuclear cells (PBMCs) isolated from the blood of healthy individuals and patients with primary (Gleason 6), mid (Gleeson 7), or distant metastasis (Gleason 9) PCa ( n = 2 per condition) showed that both CSF1 and NOS3 were significantly increased ( p < 0.05) in high-grade PCa patients (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Reproduced by permission of Smith et al 77 and Prest et al 87 kinase present on the surface of macrophages, microglia, and monocyte receptors. 84 The CSF1/CSF1R axis is associated with the proliferation, differentiation, and function of macrophages. PLX3397, a CSF1R inhibitor, reduces the number of macrophage and microglia.…”
Section: Gels/scaffolds That Deliver Signaling Moleculesmentioning
confidence: 99%
“…CSF-1R-positive macrophages correlate with poor prognosis in various solid cancers [ 102 ]. Targeting CSF-1R can effectively reduce the number of GAMs in the TME and promote GAM repolarization, thus promoting the activation of cytotoxic T-cells, inhibiting tumor growth, and preventing glioblastoma recurrence [ 103 , 104 , 105 , 106 , 107 , 108 ]. The small molecule inhibitor PLX-3397 was assessed in recurrent glioblastoma in a phase II clinical trial.…”
Section: Gam-targeted Therapy In Gbmmentioning
confidence: 99%